Hambatan Internal Guru Bimbingan dan Konseling dalam Memberikan Layanan pada Anak Berkebutuhan Khusus - Hanifah Irwan (Jurnal Counseling Care, 2019)
This research is motivated by the phenomenon of the existence of students with special needs who do not care when the Guidance and Counseling Teachers provide services and the existence of Guidance and Counseling Teachers who spend a long time to provide services to children with special needs because children have weak grasp and below average abilities. average in Vocational High School 4 Padang. The purpose of this study is to describe the internal barriers of Guidance and Counseling Teachers in providing services to children with special needs. This research is a type of qualitative research, with 4 key informants as Guidance and Counseling Teachers and 3 additional informants, namely special assistant teachers, subject teachers and school principals. The instrument of this research is to use interview guidelines in the form of structured interviews, observations and documentation studies and processed by conducting data analysis inductively-deductively. The results of the study revealed that in general the Guidance and Counseling Teacher has internal barriers in providing services to children with special needs in Padang Vocational High School 4 Padang. Guidance and Counseling teachers do not have enough knowledge about how to deal with children with special needs. The results of this study are recommended to the Guidance and Counseling Teachers to further enhance their understanding by attending training on how to deal with children with special needs and the principal to pay more attention to the facilities needed by the Guidance and Counseling Teacher in providing services to children with special needs.